A Remarkable Class of Nanocomposites: Aerogel Supported Bimetallic Nanoparticles - Gunes, Hande; Özbakir, Yaprak; Barim, S. Bengisu; Yousefzadeh, Hamed; Bozbag, Selmi E.; Erkey, Can (Frontiers in Materials, 2020)
Aerogels are a unique class of materials due to their low density, high porosity, high surface area, and an open and interconnected pore structure. Aerogels can be organic, inorganic and hybrid with a plethora of surface chemistries. Aerogel-based products for thermal insulation are already in the market and many studies are being conducted in many laboratories around the world to develop aerogel-based products for other applications including catalysis, adsorption, separations, and drug delivery. On the other hand, bimetallic nanoparticles dispersed on high surface area carriers, which have superior properties compared to their monometallic counterparts, are used or are in development for a wide variety of applications in catalysis, optics, sensing, detection, and medicine. Investigations on using aerogels as high surface area carriers for dispersing bimetallic nanoparticles are leading to development of new composite materials with outstanding properties due to the remarkable properties of aerogels. The review focuses on the techniques to synthesize these materials, their properties, the techniques to tune their pore properties and surface chemistry and the applications of these materials.